Instruction and Argumentation in Kodak's Advertising Practice: A Multilevel Analysis of The Difference - Maier, Carmen Daniela (HERMES - Journal of Language and Communication in Business, 2008)
This paper presents research findings on the use of a multilevel analytical method for the exploration of a complex text. The paper begins by describing The Difference, an advertising and instructive material of the Kodak Company, in which several semiotic modes, media, texts types and genres are functionally integrated in order to persuasively convey specialized knowledge. A presentation of the main concepts that are employed in the multilevel analysis of this complex text is also provided. Through the application of the multilevel analysis on The Difference, it is explained in detail how the instructive and argumentative discourses are actualized at the multimodal and multimedial intersection of different genres and text types. The last part of the analysis is dedicated to the presentations of the interactive connections that can be established through a multilevel analysis. The possible implications for further applications and the improvement of the method are included in the conclusions of the paper. Although it is dedicated only to the verbal mode, Virtanen’s idea of a multilevel analytical model (1992) has been employed as a starting point in the present analysis. Certainly, the model has been thoroughly expanded because, when exploring complex texts like The Difference, such a multilevel analytical model is supposed to include multimodal and multimedial dimensions.